Основні елементи адаптивної системи управління підприємством готельно-ресторанного господарства в умовах нестабільної економіки - Линник, Олена Іванівна; Жадан, Тетяна Андріївна (My University, 2019)
У статті розглянуто вплив циклічних змін факторів зовнішнього середовища на процеси ефективного функціонування та розвитку підприємств готельного та ресторанного господарства країни. Для успішного функціонування в умовах нестабільної економіки підприємства готельно-ресторанного господарства мають розробити та впровадити систему адаптивного управління. В ході дослідження проведено аналіз економічної сутності термінів «адаптація», «адаптивне управління», обґрунтовано теоретичні і методичні засади адаптивної системи управління підприємством, виділено основні етапи та напрями адаптації. Окремо підкреслено значення соціального аспекту адаптації підприємств готельно-ресторанної галузі. Особливої уваги потребують питання формування місії підприємства, його організаційної культури, ідеології, визначення лідерів колективу, розкриття потенціалу трудових ресурсів. Відзначено, що саме здатності та компетентність персоналу є силою, спроможною сформувати ефективний механізм адаптивного управління.

The article deals with the influence of cyclical changes of environmental factors on the processes of effective functioning and development of the enterprises of the hotel and restaurant economy of the country. In order to function successfully in an unstable economy, hotel and restaurant businesses need to develop and implement an adaptive management system. The processes of market environment fluctuations occurring in the domestic and world economic systems require new progressive approaches, refinement of the existing theoretical and methodological tools of the system of adaptive management of the hotel and restaurant enterprises. In the course of the research the economic essence of the terms "adaptation", "adaptive management" is analyzed, theoretical and methodological foundations of adaptive system of enterprise management are substantiated. It is stated that the enterprise should anticipate changes, react in a timely manner to the preferences of clients and adapt to them, that is, "adapt" through the application of methods, techniques and principles of management activity. The authors highlight the main stages and directions of adaptation of enterprises in the context of changes in the internal and external environment. The stages and mechanisms of implementing adaptive management in the hotel and restaurant industry can vary greatly, but they all serve the purpose of ensuring the development of the enterprise and its adaptation to external permanent changes. One of the directions of adaptation is reorganization of the enterprise, change of management system, improvement of marketing policy. The importance of the social aspect of adaptation is emphasized separately in the paper. It is emphasized that special attention is needed to formulate the mission of the hotel and restaurant enterprise, its organizational culture, ideology, determine the leaders of the collective, unlock the potential of labor resources. It is noted that the ability and competence of the staff is a force capable, provided sufficient motivation of employees, to form an effective mechanism for adaptive management of the potential of the enterprise.
Key elements of the adaptive system of management of the hotel and restaurant economy in the unstable economy
Keywords: адаптація; адаптивне управління; готельно-ресторанне господарство; нестабільна економіка; ефективне функціонування; конкурентоспроможність; соціальний аспект адаптації; adaptation; adaptive management; hotel industry; restaurant industry; unstable economy; efficient functioning; competitiveness; social aspect of adaptation